2000
DOI: 10.1046/j.1432-1327.2000.01779.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of pyc1 encoding pyruvate carboxylase isozyme I by nitrogen sources in Saccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, the existence of PYC1 and PYC2 encoding cytosolic pyruvate carboxylase isoform I and II is rather puzzling, owing to the lack of potent differential gene regulation by the carbon sources. We report several findings indicating that these two genes are differentially regulated by the nature of the nitrogen source. In wild-type cells, the activity of pyruvate carboxylase, which is the sum of pyruvate carboxylase isoform I and II, was two-to fivefold lower in carbon medium containing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It remains to be determined whether intracellular 2-OG is the induction signal for enhanced OGDH activity. It has been suggested that intracellular 2-OG concentration may regulate PYC1, encoding one isoform of pyruvate carboxylase (Huet et al, 2000), and might be a key signal for regulation of the retrograde response (RTG)-dependent pathways (Liu & Butow, 1999).…”
Section: Contribution Of the Various Pathways According To Nitrogen Smentioning
confidence: 99%
“…It remains to be determined whether intracellular 2-OG is the induction signal for enhanced OGDH activity. It has been suggested that intracellular 2-OG concentration may regulate PYC1, encoding one isoform of pyruvate carboxylase (Huet et al, 2000), and might be a key signal for regulation of the retrograde response (RTG)-dependent pathways (Liu & Butow, 1999).…”
Section: Contribution Of the Various Pathways According To Nitrogen Smentioning
confidence: 99%
“…It has also been reported that overexpression of pyruvate carboxylase, encoded by the gene PYC2 , which is responsible for synthesis of oxaloacetic acid from pyruvic acid, led to an increase in malic acid production in glucose‐limited continuous culture [100]. Furthermore, pyruvate carboxylase activity has been reported to be affected by the concentrations of many substances, such as aspartic acid, asparagine, glutamic acid, glutamine, ammonium, arginine, methionine, threonine or leucine [101], making an exploration of the metabolism of these organic acids even more difficult. Therefore the pathways which were up‐regulated or down‐regulated in the fis1 disruptant, leading to high malate production, remain unknown and open for future study.…”
Section: Metabolic Pathways That Produce Malate In Yeast During Sake mentioning
confidence: 99%